A Little-Known Dah-nāma: ʿAishī’s ʿIshrat-nāma - Beelaert, Anna Livia (Annali di Ca’ Foscari: Serie Orientale, 2019)
The present article offers an edition of the single known manuscript of ʿAishī Shīrāzī’s ʿIshrat-nāma in the Bibliothèque Nationale in Paris, Suppl. Persan 1142 (nr. 1642 in the catalogue of Blochet), a poem belonging to the mathnawī genre dah-nāma. In this genre, the evolution of the relationship of two lovers up to their union is described through their exchange of ten letters or, as is also the case here, ten verbal messages. It is argued that it was written between 874/1470 and 882/1478, namely, at the time of Aq-Quyūnlū Khalīl b. Uzun Ḥasan, during his governorship of Fārs, some seventy years later than Blochet’s estimate. This is the first of two articles about this poem. The second article, in which the messengers – ten different musical instruments who convey the messages between the lovers – shall be discussed, will be published in the next issue.